The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1083/jcb.201212089
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of high affinity HuD targets releases Kv1.1 mRNA from miR-129 repression by mTORC1

Abstract: Inhibition of mTORC1 leads to the degradation of high affinity HuD target mRNAs, freeing HuD to bind Kv1.1 mRNA and promote its translation by overcoming miR-129–mediated repression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
126
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(134 citation statements)
references
References 70 publications
7
126
1
Order By: Relevance
“…mTOR is activated upon NMDAR stimulation and mediates the repression of a number of messengers and the translational activation of others (Sosanya et al, 2013). We found that the pharmacological inhibition of mTOR or of the upstream kinase phosphoinositide 3-kinase (PI3K) with specific drugs blocked the formation of synaptic XRN1 puncta triggered by NMDA (Fig.…”
Section: Xrn1 Forms Synaptic Bodies That Are Different From Processinmentioning
confidence: 92%
See 1 more Smart Citation
“…mTOR is activated upon NMDAR stimulation and mediates the repression of a number of messengers and the translational activation of others (Sosanya et al, 2013). We found that the pharmacological inhibition of mTOR or of the upstream kinase phosphoinositide 3-kinase (PI3K) with specific drugs blocked the formation of synaptic XRN1 puncta triggered by NMDA (Fig.…”
Section: Xrn1 Forms Synaptic Bodies That Are Different From Processinmentioning
confidence: 92%
“…NMDAR stimulation affects translation through multiple mechanisms. It activates the mammalian/mechanistic target of rapamycin (mTOR), which in turn stimulates a number of translation factors and affects several miRNA targets in opposite directions (Weiler and Greenough, 1993;Banko et al, 2006;Sosanya et al, 2013). The integration of all these pathways results in the de-repression of a number of transcripts and the repression of others, and it was suggested that the reduction in the global protein synthesis rate induced by NMDA facilitates the translation of specific messengers, including that of Ca 2+ /CaM-dependent protein kinase II (CaMKII) and activity-regulated cytoskeletal-associated protein (Arc, also known as Arg3.1) mRNAs, which appear to compete poorly with other transcripts (Marin et al, 1997;Scheetz et al, 2000;Sutton et al, 2004;Sutton et al, 2006;Sutton et al, 2007;Park et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, under conditions of inactive mTOR, association of the RBP HuD with AU-rich sequences on Kv1.1 mRNA was facilitated, resulting in an activation of Kv1.1 local translation. It was further suggested that the positive effect of HuD on Kv1.1 translation is the final result of the titration of other high affinity HuD targets [37] (figure 2a). In a different study, it was shown that the RISC-associated protein MOV10 is rapidly ubiquitinated and degraded upon membrane depolarization or activation of NMDA channels.…”
Section: Regulation Of Mirnas By Neuronal Activity (A) Activity-depenmentioning
confidence: 99%
“…Many of the alcohol-responsive adaptations are related to synaptic structure and function and may be caused by coordinated changes in local mRNA translation Mayfield and Nunez, 2012). MicroRNAs are short, noncoding RNAs that can regulate the translation of many target mRNAs, and this process is known to occur in the synaptic compartments of the cell (Lugli et al, 2005(Lugli et al, ,2008Smalheiser and Lugli, 2009;Sosanya et al, 2013). The ability of microRNAs to regulate mRNAs provides a localized regulatory system that may be important in the treatment of alcoholism.…”
Section: Introductionmentioning
confidence: 99%
“…Synaptoneurosomes (SN) (Hollingsworth et al, 1985;Quinlan et al, 1999;Raab-Graham et al, 2006;Sosanya et al, 2013) contain membrane vesicles of pre-and postsynaptic compartments of neurons as well as peri-synaptic compartments of astrocytes and microglia and offer an improved model for studying the synaptic transcriptome. We recently showed that alcohol-induced mRNA changes are greater in SN compared with TH (Most et al, 2014).…”
Section: Introductionmentioning
confidence: 99%